2009
DOI: 10.1007/s12263-009-0135-4
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids and cognitive function: a review of human randomized controlled trial studies and recommendations for future studies

Abstract: Evidence in support of the neuroprotective effects of flavonoids has increased significantly in recent years, although to date much of this evidence has emerged from animal rather than human studies. Nonetheless, with a view to making recommendations for future good practice, we review 15 existing human dietary intervention studies that have examined the effects of particular types of flavonoid on cognitive performance. The studies employed a total of 55 different cognitive tests covering a broad range of cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
128
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(133 citation statements)
references
References 63 publications
(206 reference statements)
5
128
0
Order By: Relevance
“…Five short cognitive interviewer-administered tests [38,39] were administered by trained investigators at baseline and 6h on both testing occasions to determine any acute changes in cognition.…”
Section: Cognitive Tasksmentioning
confidence: 99%
See 2 more Smart Citations
“…Five short cognitive interviewer-administered tests [38,39] were administered by trained investigators at baseline and 6h on both testing occasions to determine any acute changes in cognition.…”
Section: Cognitive Tasksmentioning
confidence: 99%
“…Although previous studies have found no significant acute effect of anthocyanins from fruit source on cognitive processes, the QGP juice used in the present study had a significant higher content of anthocyanins and therefore there was a possibility that it might induce cognitive effects. In addition, two different cognitive tests that have been shown to be sensitive and target different domains were utilized; Stroop and the Reaction time task [39,56]. Extensive research has been carried out on the long term effect of flavonoid supplementation on cognition [39] with less attention on their acute effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis, flavonoid supplementation relative to a placebo control group improved cognitive performance in 9 of 15 randomised controlled trials (Macready et al 2009). Subsequent studies found that 12 weeks of wild blueberry juice supplementation (ϳ7 mg anthocyanins per kg −1 ·d −1 ) improved memory function (paired associative learning and word list recall) in adults with mild cognitive impairment (Krikorian et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is less obvious how other dietary-derived nutrients or nonnutrient components may impact on the functioning of the brain. Despite this, a large number of dietary intervention studies in humans [1] and animals [3], in particular those using foods and beverages derived from Vitis vinifera (grape), Camellia sinensis (tea), Theobroma cacao (cocoa) and Vaccinium spp (blueberry) have demonstrated beneficial effects on human vascular function and on improving memory and learning [1][2][3]. While such foods and beverages differ greatly in chemical composition, macro-and micronutrient content and caloric load per serving, they have in common that they are amongst the major dietary sources of a group of phytochemicals called flavonoids.…”
mentioning
confidence: 99%